The frequency of NUDT15 rs116855232 and its impact on mercaptopurine-induced toxicity in Syrian children with acute lymphoblastic leukemia - Muhammad, Muhammad; Saifo, Maher; Aljamali, Majd; Alali, Mousa; Ghanem, Khaled M. (Frontiers in Oncology, 2024)
Introduction: Polymorphisms in NUDT15 may result in differences in mercaptopurine-induced toxicity. This study aimed to identify the frequency of the NUDT15 (c.415C>T; rs116855232) polymorphism and investigate the effect of this polymorphism on mercaptopurine-induced toxicity in a population of Syrian patients with childhood acute lymphoblastic leukemia (ALL). Methods: This is a retrospective study that included children with ALL reaching at least 6 months of maintenance therapy. The NUDT15 genotyping was determined using standard targeted sequencing of polymerase chain reaction products. The odds ratio (OR) for the association between toxicity and genotype was evaluated. Results: A total of 92 patients were enrolled. The majority of the patients in the study population were low-risk (63.04%), followed by intermediate-risk (25%), and high-risk (11.96%). There were 5 patients (5.4%) with NUDT15 (c.415C>T; rs116855232) CT genotype, and 1 patient (1.08%) with NUDT15 TT genotype, with allele frequencies of C=0.962 and T=0.038. The mercaptopurine median dose intensity was 100%, 54.69%, and 5% for the genotypes CC, CT, and TT, respectively (P=0.009). Early onset leukopenia was significantly associated with the NUDT15 polymorphism (OR: 6.16, 95% CI: 1.11-34.18, P=0.037). There was no association between the NUDT15 genotype and hepatotoxicity. Conclusion: Approximately 6.5% of the study population exhibited reduced NUDT15 activity. The mercaptopurine dose intensity was considerably low in NUDT15 rs116855232 TT genotype compared with CT and CC. The dosage of mercaptopurine should be adjusted according to the NUDT15 genotype in pediatric patients with ALL.